Community Development within Local Wisdom Frame (The Case of Ki Ageng Tarub Cultural Kitrab, Tarub Village, Tawangharjo, Grobogan) - Ahmad Fauzi; Endang Sri Wahyuningsih; Miatun Khasanah (Universitas Islam Negeri Walisongo Semarang, 2021)
Local traditions and culture as a form of local wisdom serve as a medium to maintain and care for the harmony of the community environment. This includes harmony and unity between fellow communities when the community and nation environment is undermined by the dangers of intolerance, radicalism and terrorism. Local wisdom is one effective way to overcome it. One form of local wisdom that exists in the community is the tradition of the Ki Ageng Tarub Cultural Culture , the ancestor of the kings in Java. This research aims to reveal how the tradition of the Ki Ageng Tarub Cultural Culture can accommodate social relations between communities and even to the Surakarta palace. This research is a qualitative-exploratory, case study with an ethnographic approach and uses interactive analysis which includes data reduction, data presentation and conclusion drawing. It is hoped that in this research, it can be known about the intent, purpose and meaning of cultural culture as well as social cohesion in the frame of local wisdom in the tradition of Ki Ageng Tarub Cultural Culture.